2011
DOI: 10.1007/s13364-010-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Fennoscandian phylogeography of the common shrew Sorex araneus. Postglacial recolonisation—combining information from chromosomal variation with mitochondrial DNA data

Abstract: We examine mtDNA variation of the common shrew in Fennoscandia to explore the incongruence found in previous studies using chromosomal and mitochondrial markers, aiming to reveal post-glacial recolonisation patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
2
15
1
Order By: Relevance
“…Second, demographic, geographic, or historical factors might have a stronger effect than chromosomes in structuring the hybrid zones. In agreement with previous studies (Andersson et al 2004; Jadwiszczak et al 2006; Lundqvist et al 2011; Moska et al 2011), we observed a low genetic differentiation among chromosomal races of S. araneus . This low genetic differentiation might be explained by the recentness of chromosome differentiation, as karyotypic evolution was proposed to occur between 15,000 and 7000 years ago in the S. araneus group (Searle 1984; Wójcik 1993).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, demographic, geographic, or historical factors might have a stronger effect than chromosomes in structuring the hybrid zones. In agreement with previous studies (Andersson et al 2004; Jadwiszczak et al 2006; Lundqvist et al 2011; Moska et al 2011), we observed a low genetic differentiation among chromosomal races of S. araneus . This low genetic differentiation might be explained by the recentness of chromosome differentiation, as karyotypic evolution was proposed to occur between 15,000 and 7000 years ago in the S. araneus group (Searle 1984; Wójcik 1993).…”
Section: Discussionsupporting
confidence: 93%
“…This low genetic differentiation might be explained by the recentness of chromosome differentiation, as karyotypic evolution was proposed to occur between 15,000 and 7000 years ago in the S. araneus group (Searle 1984; Wójcik 1993). Moreover, chromosome differentiation was hypothesized to be a fast process (Andersson et al 2005; Lundqvist et al 2011), which could be largely independent of the genetic differentiations acquired in allopatry during the last glaciations (e.g., Taberlet et al 1994). In addition, recent common ancestry from a shared glacial refugium may also explain a low genetic differentiation (Jadwiszczak et al 2006; Lundqvist et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other species where the clade(s) occupying the Scandinavian peninsula were also present in central or eastern Europe [4], [22], [23]. For the field vole, one of the two source populations for the bi-directional Fennoscandian colonization had therefore originated in eastern Europe or western Asia, while the other was confined to the southern part of the Scandinavian peninsula itself.…”
Section: Introductionmentioning
confidence: 66%
“…Although more genetic evidence is needed from haplotypes in Russia and more easterly populations, this does suggest that foxes colonised Scandinavia from two different directions. This easterly and westerly colonisation into Scandinavia is observed in a range of species, including brown bears (Taberlet et al., 1998; Korsten et al., 2009), field voles ( Microtus agrestis ; Jaarola et al., 1999) and common shrews ( Sorex araneus ; Lundqvist et al., 2011), leading to a distinctive suture zone of haplotypes, as would seem evident in our cytb data. CR data are less clear as it shows much greater population differentiation.…”
Section: Discussionmentioning
confidence: 99%